2008
DOI: 10.1097/inf.0b013e3181684d67
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Persistence in Chronic Obstructive Pulmonary Disease

Abstract: Respiratory syncytial virus (RSV) is predominantly recognized as a pediatric pathogen although sensitive molecular diagnostic techniques have led to its more frequent detection in some adult settings. In some studies RSV has been detected just as frequently in stable chronic obstructive pulmonary disease (COPD) patients as in those suffering disease exacerbations, leading to the suggestion that RSV may persist in COPD. Although some studies have found negligible RSV in stable COPD, others have detected RSV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 84 publications
6
60
0
Order By: Relevance
“…These results support the hypothesis that the innate and adaptive immune response contributes to the pathology in peripheral lung lesions in COPD, but the antigens that drive this response remain to be determined (8)(9)(10)(11)(12)(13). Some have suggested that autoantigens drive the pathogenesis of COPD (14), whereas others propose that the emergence of new strains of foreign microbes (9)(10)(11)(15)(16)(17)(18) initiates a cycle of infection, inflammation, and dysfunctional repair, which drives the progression of COPD (10,15).…”
supporting
confidence: 71%
“…These results support the hypothesis that the innate and adaptive immune response contributes to the pathology in peripheral lung lesions in COPD, but the antigens that drive this response remain to be determined (8)(9)(10)(11)(12)(13). Some have suggested that autoantigens drive the pathogenesis of COPD (14), whereas others propose that the emergence of new strains of foreign microbes (9)(10)(11)(15)(16)(17)(18) initiates a cycle of infection, inflammation, and dysfunctional repair, which drives the progression of COPD (10,15).…”
supporting
confidence: 71%
“…Interestingly, chronic obstructive pulmonary disease (COPD) is associated with an exaggerated type 1 immune cell inflammatory infiltrate [7,27]. Chronic RSV infection has been reported in COPD [28] and acute COPD exacerbations are associated with RSV infection [29,30]. BORCHERS and co-workers [18,31] demonstrated that NKG2D ligand expression is induced on pulmonary epithelial cells in response to oxidative stress, and protein levels of cell-associated MICA were significantly increased in COPD patients who smoked.…”
Section: Ifn-c Increases Rsv-induced Il-15 Levels But Downregulates Rmentioning
confidence: 99%
“…Given the recent discovery of HMPV (73), it is not surprising that substantially more is known about RSV infection, and it is likely that many features linked to RSV will be similar to HMPV (45). RSV and HMPV genome have been detected in chronic obstructive pulmonary disease patients (24,25,49,61,76,78), a feature suggestive of persistent infection. In the mouse model, RSV has been shown to induce long-term airway disease characterized by chronic airway inflammation and airway hyper-reactivity, where 42 days after RSV infection reverse transcription-PCR (RT-PCR) indicated the presence of viral RNA in the lower respiratory tract, and the presence of genomic RNA persisted for months after infection (52).…”
mentioning
confidence: 99%